APPLICATION OF RESTORATIVE JUSTICE IN DRUG ABUSE (SABU) IN INDONESIA: PENERAPAN RESTORATIVE JUSTICE DALAM PENYALAHGUNAAN NARKOBA ( SABU) DI INDONESIA - Gea , Swastati (UPMI Proceeding Series, 2023)
The purpose of this study is to examine the application of restorative justice in drug abuse cases (shabu) in Indonesia and to minimize the use of methamphetamine-type illicit drugs. This research methodology uses a literature study approach (Statute Approach) by collecting literature as part of primary and secondary data. with normative juridical research methods.The results of the study show that Restorative Justice can be applied to narcotics (meth) addicts, abusers, victims of narcotics abuse, narcotics dependence, and narcotics use for 1 day. In the case of fulfilling the requirements, such as when caught red-handed by POLRI investigators and/or BNN investigators, evidence of one day's use is found and also has the results of an assessment from the integrated assessment team at each handover of case files.This study is intended to explore the application of law to methamphetamine drug abusers based on court decision PN 811/PID.SUS/2019/PN MDN.The results of this study indicate that the application of material criminal law to decisions PN 811/PID.SUS/2019/PN MDN must comply with the demands of the prosecutor community. Because in the testimony of the accused presented at trial,(1) It states that there has been a sale and purchase transaction carried out by the defendant with someone he does not know. (2) The legal considerations against the judge who imposed the criminal sanction on decision PN 811/PID.SUS/2019/PN MDN must be based on the considerations of the public prosecutor and the judge, the offender can be sentenced to life imprisonment or imprisonment for a minimum of 5 years or a maximum 20 years and a minimum fine of 1 billion rupiah or a maximum of 10 billion rupiah by applying Article 114 paragraph (1) of Law Number 35 of 2009 concerning Narcotics.The existence of an alternative settlement of cases through Restorative Justice can realize the principles of justice that is fast, simple and low-cost, as well as restoring and developing the physical, mental and social aspects of suspects, defendants or convicts in narcotics cases, which are carried out with an integrated and coordinated treatment and recovery program.